Divinest Sense : the construction of female madness and the negotiation of female agency in Sylvia Plath's The Bell Jar Jean Rhys's Wide Sargasso Sea and Margaret Atwood's Surfacing - Sandwith, Corinne (University of Pretoria, 2017)
Dissertation (MA)--University of Pretoria, 2017.